Feasibility of on-site CT-FFR analysis on cardiac photon-counting CT in evaluation of hemodynamically significant stenosis in comparison to invasive catheter angiography - Ayx, Isabelle; Lichti, Lena; Büttner, Sylvia; Papavassiliu, Theano; Sopova, Kateryna; Schönberg, Stefan; Kuru, Mustafa; Marschner, Constantin (European journal of radiology, 2025)
Objectives: Coronary CT angiography (CCTA) is an excellent tool in ruling out coronary artery disease (CAD) but tends to overestimate especially highly calcified plaques. To reduce diagnostic invasive catheter angiographies (ICA), current guidelines recommend CT-FFR to determine the hemodynamic significance of coronary artery stenosis. Photon-Counting Detector CT (PCCT) revolutionized CCTA and may improve CT-FFR analysis in guiding patients. Methods: In this single-center study, patients with obstructive CAD who underwent CCTA using PCCT and subsequent ICA were included. Delta CT-FFR was calculated by subtracting the CT-FFR values 1.8 cm before and after the stenosis, with a cut-off value of >= 0.06 indicating hemodynamic significance. Revascularization during ICA defined a stenosis as hemodynamically significant. Sensitivity, specificity, negative and positive predictive value, and diagnostic accuracy of Delta CT-FFR have been determined. Patients were followed up to evaluate the rate of major adverse cardiovascular events (MACE) 6 months after CCTA. Results: A total of 28 patients (3 female, median age 68 years) were enrolled in this study. Delta CT-FFR was pathological in all patients who underwent revascularization. No patients with normal Delta CT-FFR required stent placement. In 39.29 % of the cases, calculation of Delta CT-FFR could have prevented patients from undergoing unnecessary ICA. The positive predictive value of Delta CT-FFR for CAD RADS 4a was 66.7 %, negative predictive value 100 %, and diagnostic accuracy 74 %. Conclusion: Delta CT-FFR analysis using PCCT offers a feasible tool in identifying hemodynamically significant coronary artery stenosis and can help to reduce purely diagnostic ICA.
Online veröffentlicht: 10. Januar 2025
Gesehen am 14.04.2025